Uterine Fibroids and Adenomyosis (Comprehensive Gynecology and Obstetrics,, 2018)
This volume elucidates state-of-the-art findings of uterine fibroids and adenomyosis, incorporating expert basic knowledge. Uterine fibroids and adenomyosis are common uterine tumors in reproductive-age women. However, the pathogenesis of the tumors is still poorly understood, and both genetic and environmental factors may be involved in their generation or development. Recent research on the genomics and molecular biology of uterine fibroids and adenomyosis has facilitated a better understanding of the pathogenesis and pathophysiology of these benign tumors. Renowned experts provide detailed discussions of basic research and clinical aspects of uterine fibroids and adenomyosis in this book, from histopathology and molecular pathogenesis to diagnosis and the latest treatment of uterine fibroids, including pregnancy complications of adenomyosis. A great deal of information and a deep understanding of molecular and genetic biology have led to development of more innovative treatments of these tumors. Thus this book benefits not only oncologists, seasoned gynecologists, and obstetricians, but also molecular biologists and other basic researchers who are involved in the treatment of uterine fibroids.